Исследование электромагнитных процессов в системе "IGBT-преобразователь – тяговый двигатель" в режиме ослабления возбуждения двигателя - Синчук, Олег Николаевич; Синчук, Игорь Олегович; Ключка, Александр Сергеевич; Якимец, Сергей Николаевич; Буйвол, Б. А. (НТУ "ХПИ", 2010)
Researches of electromagnetic processes in traction electromechanical complexes of a direct current Are resulted at a pulse way of regulation of pressure of a food in a mode of easing of excitation of engines. The analytical expressions are received and are recommended for use, allowing defining parameters of composed elements of a subsystem of electric braking of a traction electrotechnical complex.
Research of electromagnetic processes in system "the IGBT-converter – the traction engine" in a mode of easing of excitation of the engine
Keywords: металлургия горная; электровоз; режим тормозной; транзистор; пульсация